Diseño e implementación de domótica en el aula 2 aplicando un sistema automatizado en la Universidad Técnica de Cotopaxi sede La Maná, año 2013 - Lozano Díaz, Luis Ángel (2015)
The reason for research is to improve the system of student meetings in the classroom 2, further help to put into practice the theoretical knowledge acquired in the institution. In applying the project, the results of the research, this system also has great practical application, because it is highly efficient and helps improve an academic area.